Lactobacillus acidophilus Exerts Neuroprotective Effects in Mice with Traumatic Brain Injury. Issue 9 (7th June 2019) - Ma, Yuanyuan; Liu, Tianyao; Fu, Jingjing; Fu, Shaoli; Hu, Chen; Sun, Bo; Fan, Xiaotang; Zhu, Jingci
ABSTRACT: Background: Traumatic brain injury (TBI) causes dysbiosis and intestinal barrier disruption, which further exacerbate brain damage via an inflammatory pathway. Gut microbiota remodeling by Lactobacillus acidophilus (LA) is a potential intervention. Objective: The aim of this study was to investigate the neuroprotective effects of LA in TBI and elucidated underlying mechanisms. Methods: C57BL/6 male mice (aged 8–9 wk) were subjected to weight-drop impact and gavaged with saline (TBI + vehicle) or LA (1 × 10 10 CFU) (TBI + LA) on the day of injury and each day after for 1, 3, or 7 d. The sham + vehicle mice underwent craniotomy without brain injury and were gavaged with saline. Sensorimotor functions were determined pre-TBI and 1, 3, and 7 d postinjury. Indexes of neuroinflammation, peripheral inflammation, and intestinal barrier function were measured on days 3 and 7. Microbiota composition was measured 3 d postinjury. The data were mainly analyzed by 2-factor ANOVA. Results: Compared with sham + vehicle mice, the TBI + vehicle mice exhibited impairments in the neurological severity score (+692%, day 3; +600%, day 7) and rotarod test (−58%, day 3; −45%, day 7) ( P  < 0.05), which were rescued by LA. The numbers of microglia (total and activated) and astrocytes and concentrations of TNF-α and IL1-β in the perilesional cortex were elevated in the TBI + vehicle mice on day 3 or 7 compared with sham + vehicle mice ( P  < 0.05) and were normalized by LA. Compared with sham + vehicle mice, the TBI + vehicle mice exhibited increased serum concentrations of endotoxin and TNF-α, and intestinal barrier permeability (D-lactate) on days 3 and 7 ( P  < 0.05), and these changes were alleviated by LA. Three days postinjury, the microbiota composition was disrupted in the TBI + vehicle mice compared with sham + vehicle mice ( P  < 0.05), which was restored by LA. Conclusion: Our results demonstrate that LA exerts neuroprotective effects that may be associated with gut microbiota remodeling in TBI mice.